A hemorheological perspective on coronary microvascular dysfunction: Association of erythrocyte parameters with angiography-derived coronary microcirculatory resistance - Abdulrahman AlQazzaz; Yanfeng Lu; Jasmine Yimeng Bao; Gary S. Mintz; Jiahao Feng; Yong Zhang; Shanshan Gao; Qiang Song; Feifei Ning; Hytham H. Al-Samawi; Mohsen Al-Manj; Mohammed Al-Asadi; et al. (PLoS ONE, 2026)
Background Coronary microvascular dysfunction (CMD) contributes to myocardial ischemia in patients both without obstructive coronary artery disease (e.g., MINOCA/INOCA) and in those with co-existing epicardial stenosis. While its etiology includes structural and functional causes. hematologic parameters have been linked to cardiovascular outcomes. However, the relationship between red blood cell (RBC) markers and microvascular resistance remains poorly characterized. We aim to evaluate whether RBC parameters are correlated with the angiography-derived index of microcirculatory resistance (angio-IMR). Methods This retrospective study evaluated the association between red blood cell (RBC) parameters and angio-IMR in patients with intermediate coronary artery disease (30%−70% stenosis). Data were analyzed from 604 patients, comprising 733 lesions; red blood cell parameters were obtained during hospitalization prior to angiography. Coronary microcirculatory resistance was derived using the AngioPlus mQFR system. Multivariable linear regression models adjusted for confounders. Subgroup analyses assessed effect modification by diabetes status, and sensitivity analyses excluded hematocrit outliers, and analyses stratified by vessel (left anterior descending (LAD), left circumflex (LCx), right coronary artery (RCA)). Results Higher RBC, Hct and Hgb were independently associated with elevated angio-IMR after full adjustment (RBC: β = 0.182, P < 0.001; Hct: β = 0.019, P < 0.001; Hgb: β = 0.006, P < 0.001). Results remained robust after excluding Hct outliers (β = 0.020, P < 0.001) and consistent across diabetic ( P = 0.007) and non-diabetic subgroups ( P = 0.012). The association was significant in non-LAD vessels (Hct: β = 0.022, P < 0.001) but not in LAD lesions (Hct: β = 0.008, P = 0.357). Conclusion Elevated RBC parameters are independently associated with increased microcirculatory resistance, particularly in non-LAD vessels. These findings suggest that RBC parameters may serve as clinically relevant markers of microvascular dysfunction, warranting further investigation into their prognostic and therapeutic implications.